Animals in the Anthropocene : critical perspectives on non-human futures (Animal publics., 2015)
The term Anthropocene is a useful device for drawing attention to the devastations wreaked by anthropocentrism and for advancing a relational model for human and non-human life. As anthropogenic change affects the more-than-human world, we must accept responsibility for the damage we have caused, and the debt we owe to non-human species.